Dede Korkut Oğuznameleri Tezcan ve Boeschoten Yayımı Üzerine Notlar - Develi, Hayati (Kitabevi, 2001)
In this paper a new edition of Kitab Dede Qorqud is criticezed and put forword some new readings on the text.
Oghuzname of the Dede Qorqud (Some Notes on the Tezcan and Boeschoten Edition)
Keywords: Turkish Language; Turkish Literature; Oghuzname; Dede Qorqud